Principles of Learning by Doing Approach and Autonomous Foreign Language Learning Approach through the Prism of Views of Check Pedagogues - Yuliya Talalay (Pedagogical Discourse, 2016)
The article focuses on the characteristics of the essence and the purpose of a «learning by doing» approach, the principle of the autonomy of learning foreign languages approach; the drawbacks of a «learning by doing» approach have been singled out; the analysis of the implementation recommendations by the Check scientists has been done.The purpose of the article is to characterize the principle of a «learning by doing» approach and the principle of an autonomous learning approach in the Check Republic. To achieve the purpose of the research certain tasks have been singled out: a). to describe the essence and of a «learning by doing» approach; b). to single out the drawbacks of a learning by doing» approach; c). to characterize the essence of the principle of an autonomous learning approach; d) to analyze the recommendations on the implementation of a «learning by doing» and an autonomous learning approach made by the Check and Danish scientists. The essence of a «learning by doing» approach may be characterized as an integral learning with an active pupil. A pupil acquires the knowledge of a foreign language by the help of his own activity to solve the tasks in a situation similar to a situation in a real life. A teacher and a pupil are involved in the process of a balanced cooperation. A pupil changes the role of a teacher and the latter becomes a partner, an advisor and an assistant. The essence of the autonomous learning approach focuses on a pupil with his abilities and individual peculiarities at the centre of a pedagogical activity.Key words: principle, «learning by doing» approach, autonomous foreign language learning approach, pedagogical activity, purpose of learning, recommendations.